2013
DOI: 10.2174/13852728113179990057
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic CO2 Reduction in Gas-Solid Regime in the Presence of Bare, SiO2 Supported or Cu-Loaded TiO2 Samples

Abstract: Both commercial and home prepared (HP) TiO2 samples have been tested for the photocatalytic reduction of CO2. (HP) TiO2 powders were prepared by using TiCl4 or Ti(OC4H9)4 as the precursors to obtain HP1 and HP2 samples, respectively. Also HP Cu-loaded and SiO2 supported TiO2 powders were prepared. The HP samples were more active than the commercial ones for the photoreduction of CO2 with and without water vapour. HP1 produced mainly formaldehyde, HP2 principally methane. Acetaldehyde was found to be the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…2 shows the alignment of the conduction bands of anatase [15], rutile [16] and GaP [5,8] with the reduction potentials of the CO 2 /CH 4 couple [17]. The reduction of carbon dioxide to methane is the most thermodynamically favorite process among all the possible ones [18].…”
Section: Resultsmentioning
confidence: 99%
“…2 shows the alignment of the conduction bands of anatase [15], rutile [16] and GaP [5,8] with the reduction potentials of the CO 2 /CH 4 couple [17]. The reduction of carbon dioxide to methane is the most thermodynamically favorite process among all the possible ones [18].…”
Section: Resultsmentioning
confidence: 99%
“…Actually, avoiding the use of a batch reactor, the substrate undergoes a lower degree of reduction as fresh CO 2 is continuously fed into the system and the produced methanol is continuously removed from the catalytic sites reducing the possibility to have over oxidation phenomena. 39 Ion chromatography analyses, performed on selected samples, revealed that traces amount of formic acid were formed in the presence of Membrane 2. Methanol formation is a multi-electronic process which, in the presence The circumstance that in our system formic acid and formaldehydes are not detected, or are present in low amounts in the case of HCOOH with Membrane 2, can be explained by the fast reaction rate of these compounds to form MeOH or by the direct methanol formation.…”
Section: Photocatalytic Reaction Measurementsmentioning
confidence: 99%
“…[36][37][38] Generally the compounds formed during the gaseous photocatalytic CO 2 reduction were CO and CH 4 39,40 whilst formic acid, formaldehyde and methanol were mainly observed during liquid phase runs. [41][42][43][44] Published papers 39,43,44 dealing with batch reactors operating in similar conditions for CO 2 photo-oxidation over TiO 2 catalyst showed methane as the main reaction product and trace of formic acid. It is worth of note that, differently from what can be found in most of the literature, in this work neither CH 4 nor CO were detected, methanol being the main product obtained.…”
Section: Photocatalytic Reaction Measurementsmentioning
confidence: 99%
“…Comparing the two profiles, the TiO 2 sample provides sharper and more defined peaks than MIRKAT 211, indicating a higher crystallinity in the former sample. As a matter of fact, the MIRKAT 211 manufacturer states that this product is made up of 40 wt % anatase, while the rest is amorphous TiO 2 [55,56]. Instead, according to Rietveld analysis, it is composed of 98 wt % anatase and the remaining part is amorphous.…”
Section: Materials Characterisationmentioning
confidence: 99%
“…As a matter of fact, the MIRKAT 211 manufacturer states that this product is made up of 40 wt % anatase, while the rest is amorphous TiO2 [55,56]. Instead, according to Rietveld analysis, it is composed of 98 wt % anatase and the remaining part is amorphous.…”
Section: Materials Characterisationmentioning
confidence: 99%